Bio-Environmental preparation of chitosan nanoparticle using Bacillus subtilis and their biomedical activity - Ali, Zahraa Hussein; Aldujaili, Nawfal Hussein (IOP conference series. Earth and environmental science, 2022)
The aim of this study was to study the biomedical activity (antibacterial, antibiofilm, and antioxidant activity) and Characterization of Chitosan NPs synthesized by B. subtilis. Different types of bacterial strains(Z1-Z25) were screened for biosynthesis of chitosan NPs, Isolate (Z2) was selected as efficient isolate based on color change and antibacterial activity against the pathogenic bacteria, and it was diagnosed as Bacillus subtilis , depending on the morphology, microscopic examination and VITEK2 compact system. The characterization of biogenic chitosan NPs was achieved, using: UV visible spectrophotometry was used to describe the synthesis of chitosan NPs by B. subtilis , with an absorption peak at 280nm wavelength. SEM analysis showed the spherical, homogenous with average sizes from 29-51nm. The elemental analyses of biogenic chitosan with EDS showed 33.31% carbon, 10.24 % nitrogen, 50.55% oxygen, 5.34% phosphate and 0.55% chloride. The size and structurer of biogenic chitosan NPs was measured using XRD that appeared at 20°-26°’ AFM analysis showed the average diameter of the biogenic chitosan NPs was 47. 18. The antibacterial activity was studied for biogenic chitosan against pathogenic bacteria (P.aeruginosa, S. aureus, K. pneumonia, E.coli , and P. mirabilis). Biogenic chitosan NPs with deferent concentration (100, 200, 400ug/ml) showed inhibition against all tested bacteria and largest inhibition zone against S. aureus(26mm) with concentration 400 μg/ml. Biogenic chitosan expressed high significant antibiofilm activity with increasing concentration of chitosan NPs. DPPH reducing activity of nanoparticles which increased with increase concentration of biogenic chitosan NPs.